(untitled) (Fiep Bulletin - online, 2016)
As foreseen in the 1988 Federal Constitution, the State is responsible for the investment in order sports practices by citizens. However, it notes that the Law 11,438, known as "Law of Sports Incentive" allows individuals and companies to contribute to sport through tax deduction at 6% and 1% respectively. It turns out that the quality of the projects presented at the Ministry of Sport is low, which brings a high percentage of failure. Allied to this, when approved, the amount of funds collected and the need provided for in clash project, making their applicability labored. To improve the quality and amount of funds raised by the Sports Incentive Law suggested the qualification of physical education teachers, bringing them to do so, multidisciplinary and interdisciplinary knowledge necessary for the proper development projects.